Underwater noise from airplanes: An overlooked source of ocean noise - Erbe, Christine; Williams, R.; Parsons, Miles; Parsons, S.; Hendrawan, I.; Dewantama, I. (Elsevier, 2018)
The effects of underwater noise pollution on marine life are of increasing concern. Research and management have focussed on the strongest underwater sound sources. Aerial sound sources have understandably been ignored as sound transmits poorly across the air-water interface. However, there might be situations when air-borne noise cannot be dismissed. Commercial passenger airplanes were recorded in a coastal underwater soundscape exhibiting broadband received levels of 84–132 dB re 1 µPa rms. Power spectral density levels of airplane noise underwater exceeded ambient levels between 12 Hz and 2 or 10 kHz (depending on site) by up to 36 dB. Underwater noise from airplanes is expected to be audible to a variety of marine fauna, including seals, manatees, and dolphins. With many of the world's airports lying close to the coast, it is cautioned that airplane noise not be ignored, in particular in the case of at-risk species in small, confined habitats.